Comparison Between One Stage Correction of Vestibular Fistula by Transfistula Anorectoplasty (TFARP) and Anterior Sagittal Anorectoplasty (ASARP) (Journal of Paediatric Surgeons of Bangladesh, 2014)
Background: Various innovative approach have been tried for the surgical management of vestibular fistula, most of them have post operative complication like wound infection, wound dehiscence, more hospital stay which compromise the functional out come, financial burden and aesthetic appearance of the perineum. This article details a new technique, Transfistula Anorectoplasty (TFARP), which includes minimal dissection without interruption of perineal body and perineal skin.Materials and methods: This cross sectional comparative study on 43 patients with vestibular fistula conducted in Dhaka Shishu (Children) Hospital from September 2008 to April 2010, about 20 months. Patients were operated according to parent choice after obtaining informed consent and standard bowel preparation. Data on demographics, operation time and ostoperative complications were analyzed systematically by SPSS program. Patients were followed up for a period of 2½ months postoperatively.Results: There is no statistical difference in patient population regarding age, geographical distribution and clinical presentation. Mean operation time was 76.5 min for TFARP and 84.34 min for ASARP. Two cases had wound infection after TFARP operation and 11 patients after ASARP operation. One patient developed partial wound dehiscence after TFARP and was healed after conservative treatment within 7 days. On the other hand 5 patients developed partial wound dehiscence and 4 patients developed complete wound disruption after ASARP which were also treated conservatively need more than 02 week on an average. Mean hospital stay were 6.45 days after TFARP operation and mean hospital stay were 7.87 days after ASARP peration. Twenty neonates and infant who were treated by TFARP operation have good bowel movement without laxative and symmetrical anal contraction after stimulation.Conclusion: TFARP is an operation which produces less morbidity and is more effective and superior procedure than that of ASARP operation and gives better aesthetic appearance of the perineum.DOI: http://dx.doi.org/10.3329/jpsb.v1i2.19525